A UPLC–MS/MS method for quantification of 5α-androst-3β, 5, 6β-triol in human plasma: development, validation and its application in clinical pharmacokinetic study. (June 2017) - Wang, Zhenlei; Wang, Huanhuan; Hu, Pei; Jiang, Ji; Zhao, Qian
Aim: 5α-androst-3β, 5, 6β-triol is a novel ischemic stroke drug under clinical development. The objective of this study was to develop and validate a simple ultraperformance liquid chromatography tandem mass spectrometry method for 5α-androst-3β, 5, 6β-triol in human plasma and its application in clinical pharmacokinetic study.Methodology & results: After being pretreated using an automatized solid-phase extraction procedure, plasma sample was separated on a Waters ® Acquity™ BEH C18 column (2.1 × 50 mm id, 1.7 mm) by an Acquity UPLC system and detected by an API 5500 triple quadrupole mass spectrometer, which was validated following international guidelines.Conclusion: A simple method was successfully validated over a concentration range of 2.00–500 ng/ml for 5α-androst-3β, 5, 6β-triol and applied to investigate its plasma pharmacokinetic profiles in healthy Chinese subjects.